Fat Oxidation of Fatty Fish vs. Meat Meal Diets Under in vitro Standardized Semi-Dynamic Gastric Digestion - Harahap, Iskandar Azmy; Sobral, Maria Madalena C.; Casal, Susana; Pinho, Susana C. M.; Faria, Miguel A.; Suliburska, Joanna; Ferreira, Isabel M. P. L. V. O. (Frontiers in Nutrition, 2022)
Meat and fish are introduced in diet as source of protein, but these muscle foods present different fatty acid (FA) composition and different lipid stability. Fatty fish is expected to oxidize due to its higher content in polyunsaturated FA (PUFA), whereas the higher heme-Fe content of red meat will also affect lipid stability. Combining other food ingredients within a meal also influences lipid oxidation, which will not stop after meals intake. This is due to the acidic environment of stomach together with the presence of metallic ions, a process that is scarcely understood. The goal of this study was to evaluate the oxidation of fatty fish vs meat meal diets under in vitro standardized semi-dynamic gastric conditions and FA release from stomach to duodenum. Meal diets composed by 25% beef (BM) or fatty fish (FM), 25% fried potatoes, and 50% sugar soft drink were prepared. Proximate composition, FA and amino acid profiles, and meals quality indices were evaluated. Their differences in composition led to different total gastric digestion time of 242.74 (BM) and 175.20 (FM). Using the INFOGEST semi-dynamic gastric model, 4 GE were simulated in both meals. In each gastric emptying (GE), FA profile and lipid oxidation products (LOPs) formation were assessed. As results, more than 50% FA release to duodenum occurred in GE1, whose percentage decreased with the time of digestion. FM exhibited the highest LOPs formation, which corroborates the high peroxidisability index measured for this meal diet. Higher LOPs formation occurred in the later GEs, which released less FA. This suggests that higher times of residence in the stomach increase FA oxidation. This study shows a higher formation of LOPs during digestion of FM using a whole meal approach. These results relate to its richness in PUFAs compared to BM. Despite higher LOPs formation, FM digests that reached duodenum, still contain higher content of unoxidized PUFAs compared to BM and a desirable ꙍ3/ꙍ6 PUFAs ratio of ~0.43. LOPs formation in PUFA-rich meals could be reduced if those meals have a low caloric value, avoiding large times of residence in the stomach and consequently high levels of oxidation.